2016
DOI: 10.1186/s13741-016-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

A perioperative consult service results in reduction in cost and length of stay for colorectal surgical patients: evidence from a healthcare redesign project

Abstract: BackgroundA major restructuring of perioperative care delivery is required to reduce cost while improving patient outcomes. In a test implementation of this notion, we developed and implemented a perioperative consult service (PCS) for colorectal surgery patients.MethodsA 6-month planning process was undertaken to engage key stakeholders from surgery, nursing, and anesthesia in a healthcare redesign project that resulted in the creation of a PCS to implement a coordinated clinical pathway. After Institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…A limitation of our study is that the comparison group is a historical group and not a synchronous group, which should encourage caution in the final conclusions. Nevertheless, similar results have been published regarding laparoscopic colorectal surgery [4]. Various studies of laparoscopic left colon resection for diverticular disease described a median hospital stay of 7 days, with 4% of redo surgery (8 patients/205) [11], or an average hospital stay of 9 days, with 3% of suture leak and 2% of redo surgery [12].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…A limitation of our study is that the comparison group is a historical group and not a synchronous group, which should encourage caution in the final conclusions. Nevertheless, similar results have been published regarding laparoscopic colorectal surgery [4]. Various studies of laparoscopic left colon resection for diverticular disease described a median hospital stay of 7 days, with 4% of redo surgery (8 patients/205) [11], or an average hospital stay of 9 days, with 3% of suture leak and 2% of redo surgery [12].…”
Section: Discussionsupporting
confidence: 64%
“…By rethinking the management of patients and introducing a CP specific to laparoscopic left colectomy, we have shown that the quality of care is increased, without affecting the rate of complications which remains low compared to those published in the literature [4,8,[11][12][13][14], and the hospital stay is significantly reduced (Tables 5 and 6). A limitation of our study is that the comparison group is a historical group and not a synchronous group, which should encourage caution in the final conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true as some ERPs may attempt to avoid IV-PCA opioids and thus use opioids only as PRN rescue, as recommended in Part 2 (McEvoy et al 2016; Wu et al 2015). It should be explained to patients that opioids still remain an important option for postoperative pain management; however, the precise role of opioids in ERPs is currently not clearly defined, and expectations surrounding their use in the perioperative, along with the goals of delivering optimal analgesia, should be clarified preoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…As recent evidence shows that massive reductions in perioperative opioid use are not only possible but also associated with improved outcomes, 18 it is time for our specialty to lead the way in promoting a safe pathway for low or no-opioid perioperative analgesia. The evidence espousing the dangers of the status quo use of opioids as a primary analgesic in the postoperative period continues to mount.…”
mentioning
confidence: 99%